If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ax + cx = b Reorder the terms: cx + xA = b Solving cx + xA = b Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1xA' to each side of the equation. cx + xA + -1xA = b + -1xA Combine like terms: xA + -1xA = 0 cx + 0 = b + -1xA cx = b + -1xA Divide each side by 'x'. c = bx-1 + -1A Simplifying c = bx-1 + -1A Reorder the terms: c = -1A + bx-1
| 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= | | P=r+s-p | | x^2+36x+27= | | 4a^2-12a-7=0 | | 6-2*7=4x-6x-3 | | 10y+(3y+11)=180 | | 18-6a=12 | | 0=x+7-32 | | 35.00+0.75x=20 | | 5m+6n=64 |